2020
DOI: 10.3390/cancers12040957
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Radiotherapy Benefits and Immune Infiltration in Multiple Human Cancers

Abstract: Response to radiotherapy (RT) in cancers varies widely among patients. Therefore, it is very important to predict who will benefit from RT before clinical treatment. Consideration of the immune tumor microenvironment (TME) could provide novel insight into tumor treatment options. In this study, we investigated the link between immune infiltration status and clinical RT outcome in order to identify certain leukocyte subsets that could potentially influence the clinical RT benefit across cancers. By integrally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…According to the immune score and whether they had epilepsy, all patients were divided into four groups: C1(high immune score, seizure), C2 (high immune score, non-seizure), C3 (low immune score, seizure), and C4 (low immune score, non-seizure). Here, the immune scores that were >0 were considered high while immune scores that were <0 were considered low (Wen et al, 2020). Through survival analysis, we found that a high immune score suggested a poor prognosis in LGG patients with epilepsy (p = 0.0025, Figure 2A).…”
Section: The Level Of Immune Infiltration Affected the Prognosismentioning
confidence: 98%
“…According to the immune score and whether they had epilepsy, all patients were divided into four groups: C1(high immune score, seizure), C2 (high immune score, non-seizure), C3 (low immune score, seizure), and C4 (low immune score, non-seizure). Here, the immune scores that were >0 were considered high while immune scores that were <0 were considered low (Wen et al, 2020). Through survival analysis, we found that a high immune score suggested a poor prognosis in LGG patients with epilepsy (p = 0.0025, Figure 2A).…”
Section: The Level Of Immune Infiltration Affected the Prognosismentioning
confidence: 98%
“…Patients with high risk scores had significantly reduced number of plasma cells, activated CD4 memory cells, follicular helper T cells, and resting dendritic cells and increased number of naïve CD4 T cells, monocytes, M2 macrophages, and resting mast cells. Activated CD4 memory cells were associated with favorable outcomes in patients with cervical cancer ( Ju et al, 2020 ) and favorable outcomes after radiotherapy in patients with multiple cancers ( Ju et al, 2020 ; Wen et al, 2020 ). In gastric cancer, patients with low risk scores had increased number of activated CD4 memory cells and had superior prognosis ( Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy, either as monotherapy or as part of combination therapy, is used for the localized treatment of malignancies. According to a review article on cancers, the infiltration rate of activated memory CD4 + T cells and activated mast cells in the immune TME under radiotherapy are closely related to overall survival in multiple cancers [ 51 ]. In a mouse model of breast cancer, the combination of localized radiotherapy with CTLA-4 blockade for poorly immunogenic metastatic cancers refractory to anti-CTLA-4 monotherapy significantly improved survival [ 52 ].…”
Section: Combination Of Icis and Radiotherapymentioning
confidence: 99%